2019
DOI: 10.1155/2019/4019619
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Increases Bone Mass around the Prostheses of OVX Rats by Ameliorating Mitochondrial Oxidative Stress via the SIRT3/SOD2 Signaling Pathway

Abstract: Bone mass loss around prostheses is a major cause of implant failure, especially in postmenopausal osteoporosis patients. In osteoporosis, excess oxidative stress largely contributed abnormal bone remodeling. Melatonin, which is synthesized from the pineal gland, promotes osteoblast differentiation and bone formation and has effectively been used to combat oxidative stress. Thus, we determined if melatonin can inhibit oxidative stress to promote osteogenesis and improve bone mass around prostheses in osteoporo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 59 publications
(51 reference statements)
5
42
0
2
Order By: Relevance
“…4 D and E). In contrast, in normal cells, melatonin is known to upregulate the expression of SIRT3-SOD2 to reduce the oxidative damage [ [30] , [31] , [32] ]. To confirm that the responses of cancer cells to Mel treatment is the opposite of its effects in normal cells, we examined the effect of Mel treatment in normal cells (BHK, Vero, NIH3T3, and HaCaT) under oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 D and E). In contrast, in normal cells, melatonin is known to upregulate the expression of SIRT3-SOD2 to reduce the oxidative damage [ [30] , [31] , [32] ]. To confirm that the responses of cancer cells to Mel treatment is the opposite of its effects in normal cells, we examined the effect of Mel treatment in normal cells (BHK, Vero, NIH3T3, and HaCaT) under oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…All these effects were reversed by treatment with a ROS scavenger, suggesting that excessive oxidative stress plays a key role in Mel-SHK-induced cytotoxicity in cancer cells. Several studies have reported that Mel treatment induces cell death in cancer cells but has beneficial effects on normal cells [ [30] , [31] , [32] , 43 , 44 ]. This is probably because Mel induces the release of mitochondrial cytochrome C, leading to apoptosis in cancer cells [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2, known as GA-binding protein, binds with PGC-1α to regulate the expression of oxidative genes including Sirt3 [12]. Sirt3 in turn regulates the expression of SOD2 and mediates its protective effects against ROS and mitochondrial oxidative stress [8,32,33] by transforming Ac-SOD2 into SOD2 [34]. Further, the Nrf-2a subunit was shown to directly bind to the Sirt3 promoter, and therefore, knockdown or overexpression of Nrf-2 could modulate Sirt3 levels in vitro system [12].…”
Section: Discussionmentioning
confidence: 99%
“…Takechi et al [54] reported that MT promoted osseointegration around tibial titanium implants in Wistar rats. Zhou et al [55] showed that MT can accelerate bone formation around dental titanium implants. Therefore, the systemic administration of MT is a potential treatment for diseases such as osteoporosis that involve low bone density throughout the skeletal system.…”
mentioning
confidence: 99%